2018
DOI: 10.1007/s11657-018-0448-2
|View full text |Cite|
|
Sign up to set email alerts
|

Estimated expenditures for hip fractures using merged healthcare insurance data for individuals aged ≥ 75 years and long-term care insurance claims data in Japan

Abstract: This is the first study to estimate healthcare and long-term care expenditures post-hip fracture using claims data in Japan. Further studies are needed that include healthcare claims data at both DPC/PDPS and non-DPC/PDPS hospitals to capture the lifelong course of long-term care required post-hip fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Indeed, the previous studies based on claims data from one city in Japan suggested that there is a trade-off between medical and LTC expenditures; hence, it is important to include both medical and LTC expenditures when the societal financial burden from multiple diseases is evaluated. 22 , 34 At the time of this analysis, however, national medical insurance claims data could not be merged with national LTCI claims data in Japan. If such a procedure is available in the future, further study, including both medical insurance and LTCI claims data, would be warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the previous studies based on claims data from one city in Japan suggested that there is a trade-off between medical and LTC expenditures; hence, it is important to include both medical and LTC expenditures when the societal financial burden from multiple diseases is evaluated. 22 , 34 At the time of this analysis, however, national medical insurance claims data could not be merged with national LTCI claims data in Japan. If such a procedure is available in the future, further study, including both medical insurance and LTCI claims data, would be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the variables capturing medical spending 22 were included. These were medical expenditure per capita, inpatient medical spending per citizen ≥75 years old and outpatient medical spending per citizen ≥75 years old.…”
Section: Methodsmentioning
confidence: 99%
“…We obtained medical insurance claims data of the Late-Stage Medical Care System for the Elderly (i.e., adults ≥75 years) and LTC insurance claims data from the municipal government of Kashiwa City: a suburb in the Tokyo metropolitan area. Kashiwa City had a population of approximately 405,000 in 2012 with 8.7% of the population being at least 75 years old in October 2012 [20]. Insurance claims data for the period between April 2012 and September 2013 were available for analysis at the time of this study.…”
Section: Methodsmentioning
confidence: 99%
“…We included medical insurance claims data from both Diagnosis Procedure Combination/Per-Diem Payment Systems (DPC/PDPS) and non-DPC/PDPS. DPC/PDPS was introduced in Japan in 2003, and it offers a case-mix payment system for acute inpatient care according to diagnoses and procedures [20].…”
Section: Methodsmentioning
confidence: 99%
“…This study identified all diseases recorded in the claims for hospital admissions. The diseases with a “suspicious” flag in the claims datasets were excluded from the comorbidities because they were used to justify diagnostic procedures at non-DPC/PDPS hospitals with a fee-for-service payment system [ 28 ]. The comorbidities were categorized by ICD-10 codes for the Charlson Comorbidity Index (CCI) [ 29 , 30 ], as well as underlying diseases [ 17 ].…”
Section: Methodsmentioning
confidence: 99%